Geochemical proxy of some chemical elements in sediments of Kemaman River Estuary,Terengganu, Malaysia - Kamaruzzaman Yunus,; Ong, Meng Chuan (Universiti Kebangsaan Malaysia, 2009)
The concentrations of heavy metals (Mn, Co, Cu and Cr) were determined in the surface sediments from Kemaman River estuary using Inductively Coupled Plasma – Mass Spectrometry (ICP-MS). The relationship of heavy metal content with sediment particles size was studied. The average concentration of heavy metals are 597.8 μg/g dry weight, 16.0 μg/g dry weigh, 48.8 μg/g dry weight and 100.4 μg/g dry weight for Mn, Co, Cu and Cr, respectively. All metals showed low Enrichment Factor (EF) values (EF<1) when compared with Al which indicates that the elements in the sediment originated predominantly from crustal material or terigenous in origin. This study shows that there is a positive correlation between the mean particle size and the studied elements.